Wave diffraction and radiation studies of the array of the cylindrical bait boxes with porosities in the middle of the column wall surface under wave action. (15th June 2023) - Wang, C.; Cao, J.X.; Wang, X.; Dong, C.R.; Yu, F.J.
Abstract: In this paper, we study theoretically wave diffraction and radiation studies of the array of cylindrical bait boxes with porosities in the middle of the column wall surface under wave action. The middle position of each cylindrical bait box column wall surface is the region with holes, and the upper and lower ends of the cylindrical bait box column wall surface are the region without holes. Under the assumption of the linear theory of potential flow, the eigenfunction expansion method, Bessel's function addition theory, and Darcy's law are used to investigate the wave diffraction and radiation of the array of cylindrical bait boxes with porosities in the middle of the column wall surface. Then, the related analytical expressions for velocity potential and free surface elevation are derived. After the validation process, a detailed parametric study is carried out. Porosity, spacing, porous area size, and incident wave angle are systematically adjusted, and their effects on wave force, added mass, radiation damping coefficient, and wave height are investigated. The related phenomena are also explored. It is found that the variation of porosity coefficient and porous area size greatly influence the cylindrical bait boxed, which can efficiently bait while reducing drag. The study results can help the designer/engineer to design the bait boxes with better structural performance and achieve more rational and better baiting. Highlights: Wave diffraction and radiation studies of the array of the cylindrical bait boxes. Theory of potential flow. The bait boxes with porosities in the middle of the column wall surface. Porosity has a significant effect on the horizontal and vertical components of the bait boxes. The reflection phenomenon on the upper wave side is obvious at higher frequencies.